2015
DOI: 10.3389/fevo.2015.00109
|View full text |Cite
|
Sign up to set email alerts
|

Activity level and aggregation behavior in the crustacean gammarid Gammarus insensibilis parasitized by the manipulative trematode Microphallus papillorobustus

Abstract: Hosts manipulated by parasites are profoundly altered organisms exhibiting a broad range of potential modifications. Exploring this multidimensionality is an emerging field. Previous studies have shown that the bird trematode Microphallus papillorobustus induces several behavioral changes in the gammarid Gammarus insensibilis. Knowing that aggregation behavior and reduced activity levels are strategies that limit predation in other species of amphipods, we explored in this study these behavioral responses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Aberrant escape behaviour occurs in response to disturbance (Ottaviani & Franceschi, 1996). Arnal et al (2015) reported greatest activity by infected G. insensibilis in the presence of fish slime and bird faeces, both associated with potential definitive hosts. In the current study disturbance was minimal in the laboratory assay so activity may be reduced in the infected animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aberrant escape behaviour occurs in response to disturbance (Ottaviani & Franceschi, 1996). Arnal et al (2015) reported greatest activity by infected G. insensibilis in the presence of fish slime and bird faeces, both associated with potential definitive hosts. In the current study disturbance was minimal in the laboratory assay so activity may be reduced in the infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the effects of trematode infection on reproduction were probably initiated prior to the release of eggs into the marsupium, perhaps because of reduced energy to allocate to reproduction. Increased activity by hosts generated by manipulative parasites (Arnal et al ., 2015), melanization and encapsulation responses induced following infection (Kostadinova & Mavrodieva, 2005b) and wounding and haemolymph loss through penetration of the abdomen by cercariae (Fredensborg et al ., 2004) are probably energetically costly, reducing resources available for reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of parasites on host behaviour are similarly difficult to generalize. Parasite infection is related to both increased and decreased grouping behaviours (Arnal et al, 2015; Barber & Huntingford, 1995; Krause & Godin, 1994; Spagnoli et al, 2015), foraging (Barber et al, 2000; Meadows & Meadows, 2003), movement (reviewed in Binning et al, 2017) and activity (Arnal et al, 2015; Binning et al, 2017). As a result, ignoring parasite infection in studies of host performance can lead to biases, misinterpretations and erroneous conclusions that can be impossible to account for post‐hoc (Timi & Poulin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of parasites on host behaviour are similarly difficult to generalize. Parasite infection is related to both increased and decreased grouping behaviours (Arnal et al, 2015;Barber & Huntingford, 1995;Krause & Godin, 1994;Spagnoli et al, 2015), foraging (Barber et al, 2000;Meadows & Meadows, 2003), movement (reviewed in Binning et al, 2017), and activity (Arnal et al, 2015;Binning et al, 2017). As a result, ignoring parasite infection in studies of host performance can lead to biases, misinterpretations and erroneous conclusions that can be impossible to account for post-hoc (Timi & Poulin, 2020).…”
Section: Introductionmentioning
confidence: 99%